A new strategy for detecting dopamine in human serum using polymer brushes reinforced with carbon nanotubes - Recco, Lucas C. [UNESP]; Crulhas, Bruno P. [UNESP]; Parra, João P. R. L. L. [UNESP]; Pedrosa, Valber A. [UNESP] (Royal Society of Chemistry (RSC), 2016)
Direct detection of dopamine (DA) in serum samples without any type of extraction or pre-treatment has been a great challenge for biomedical analysis. This paper reports the development of a sensor consisting of polymer brushes reinforced with multi-walled carbon nanotubes, that was used to determine levels of dopamine in human blood serum. The structure and morphology of the as-prepared hybrid nanomaterials were characterized and confirmed by scanning electron microscopy and electrochemistry techniques. This methodology employs differential pulse voltammetry to detect dopamine in human serum samples at concentrations ranging from 0.1 μM to 10 μM with an obtained detection limit of 40.5 nmol L-1 (R = 0.996). This sensor provides an inexpensive and easy-to-use device with high degrees of sensitivity and selectivity for monitoring DA in human blood serum samples.